2006
DOI: 10.2193/0022-541x(2006)70[1200:paaoba]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Absence of Bats Across Habitat Scales in the Upper Coastal Plain of South Carolina

Abstract: During 2001, we used active acoustical sampling (Anabat I/) to survey foraging habitat relationships of bats on the Savannah River Site (SRS) in the upper Coastal Plain of South Carolina. Using an a priori information-theoretic approach, we conducted logistic regression analysis to examine presence of individual bat species relative to a suite of microhabitat, stand, and landscape-level features such as forest structural metrics, forest type, proximity to riparian zones and Carolina bay wetlands, insect abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 36 publications
5
78
4
Order By: Relevance
“…In addition to the increased biological diversity inherent in the juxtaposition of aquatic and terrestrial habitats (Crow et al, 2000;Sabo et al, 2005), riparian zones have been shown to be unique from adjacent upland forest. Differences in vegetative composition (Goebel et al, 2003;Hagan et al, 2006) and in use by invertebrates (Rykken et al, 2007b), amphibians (Pauley et al, 2000;Perkins and Hunter, 2006;Crawford and Semlitsch, 2007), birds (DeGraaf and Yamasaki, 2000;Bub et al, 2004) and mammals (DeGraaf and Yamasaki, 2000;Ford et al, 2006) have been reported. The unique habitat qualities of riparian zones have been ascribed, in part, to their microclimatic conditions (Brosofske et al, 1997;Moore et al, 2005;Olson et al, 2007;Rykken et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increased biological diversity inherent in the juxtaposition of aquatic and terrestrial habitats (Crow et al, 2000;Sabo et al, 2005), riparian zones have been shown to be unique from adjacent upland forest. Differences in vegetative composition (Goebel et al, 2003;Hagan et al, 2006) and in use by invertebrates (Rykken et al, 2007b), amphibians (Pauley et al, 2000;Perkins and Hunter, 2006;Crawford and Semlitsch, 2007), birds (DeGraaf and Yamasaki, 2000;Bub et al, 2004) and mammals (DeGraaf and Yamasaki, 2000;Ford et al, 2006) have been reported. The unique habitat qualities of riparian zones have been ascribed, in part, to their microclimatic conditions (Brosofske et al, 1997;Moore et al, 2005;Olson et al, 2007;Rykken et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic surveys can be conducted in areas where capturing bats with the traditional method of mist netting is difficult (that is within parks). The present data collected by acoustics has been successfully used to model species presence in association with habitat characteristics in a number of other studies (Brooks and Ford, 2005;Erickson and West, 2003;Ford et al, 2005;Ford et al, 2006;Francl et al, 2004;Loeb and O'Keefe, 2006;Zimmerman and Glanz, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…Previous models for predicting bat distributions have often been conducted at the landscape scale, which by their nature are relatively coarse, placing up to 1 km buffers around survey points (Ford et al, 2006). A focus on this large scale provides limited insight into the characteristics of the area immediately surrounding the foraging environment and this intermediate macro habitat (Saab, 1999) scale is often the target of management within protected areas (Abella et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…ESHs are important foraging sites for a number of North American bat species as they provide areas with abundant insects and reduced clutter, allowing for unobstructed flight and reduced 'noise' when echolocating [40][41][42]. For example, six of 15 bat species found in the Central Hardwoods Region [42], three of four bat species groups in Ontario, Canada [43], four of four bat species in the Piedmont of Georgia [44], three of three bat species groups in the managed forests of Ohio [45], and three of seven bat species in the managed forests of Indiana [46] commonly forage in open areas or their edges.…”
Section: Bat Conservation and Forestrymentioning
confidence: 99%